Prevalence and Therapeutic Relevance of Bunium mauritanicum in Algerian Ethnomedical Practices Targeting Thyroid Disorders - Khither, Hanane; Madoui, Soraya; Houchi, Selma; Nouioua, Wafa; Guergui, Rayenne; Djenane, Assala; Mosbah, Asma (Ethnobotany Research and Applications, 2026)
Background: Herbal medicine plays a significant role in managing endocrine disorders in Algeria, particularly thyroid diseases, which are more common among women. Although traditional remedies are widely used, systematic documentation of medicinal plants employed for thyroid conditions remains limited. Recording this knowledge is essential for preserving ethnomedical practices and supporting future therapeutic research. Methods: A cross-sectional ethnobotanical survey was conducted in the Setif region of Algeria using semi-structured questionnaires administered to 70 respondents. Participants included 81.43% women and 18.57% men, with 57.3% aged 20–31 years. Information collected covered plant species used, preparation methods, plant parts utilized, and routes of administration. Results: The study documented 19 plant species traditionally used for thyroid disorders. Bunium mauritanicum, (Talghoda) was the most frequently cited species (33.33%), demonstrating its central role in local ethnomedical practices. It was followed by Saussurea costus (14.67%), Atriplex halimus (10.67%), and Brazil nut (8%). Most respondents (74.7%) used single-plant preparations, whereas 25.3% used mixtures. The whole plant was most commonly employed (38.7%), followed by roots and leaves (14.7%), seeds (13.3%), fruits (10.7%), and stems (6.7%). Fresh plant material predominated (74.7%), and all remedies were administered orally. Conclusions: The findings highlight the prevalence and therapeutic relevance of Bunium mauritanicum,in traditional thyroid disorder management in Sétif. The strong reliance on herbal remedies reflects both accessibility and the depth of indigenous knowledge. This documentation supports the preservation of ethnomedical practices and offers a basis for future pharmacological investigations. Keywords: Ethnobotany; medicinal plants, phytotherapy, Bunium mauritanicum, thyroid diseases, Herbal medicine.